Characterization of the novel HLA‐C*06:346 allele by two next‐generation sequencing methods. (3rd January 2022) - Walencik, Alexandre; Calvo De Olmos, Orane; Bonneville, Francoise; Blanchet, Gaelle; Cesbron‐Gautier, Anne
Abstract : The novel HLA‐C*06:346 allele was characterized using two next generation sequencing technologies.